Phakic intraocular lenses: an update and review for the treatment of myopia and myopic astigmatism in the United States. Issue 5 (27th September 2022) - Moshirfar, Majid; Webster, Court R.; Ronquillo, Yasmyne C.
Abstract : Purpose of review: To review all phakic intraocular lenses (pIOLs) available in the United States for the correction of myopia or myopic astigmatism and offer a clinical approach to their proper use, postoperative follow-up, and analysis of visual and adverse outcomes. Recent findings: In March 2022, the FDA approved the EVO/EVO+ Visian ICL for widespread use, adding this lens to the two others available (Verisyse, Visian ICL). Cataract formation, endothelial cell loss (ECL) and surgical reintervention remain the most common adverse events. There are discrepancies between studies on ECL following implantation with pIOLs, although trends can be deduced with meta-analysis. Posterior Chamber-pIOLs (PC-pIOLs), especially the EVO/EVO+, have an overall lower mean adverse effect and subjective patient symptom profile when compared to Iris Fixated-pIOLS (IF-pIOLs). Advancements in PC-pIOL sizing have provided a noticeable difference in visual and safety outcomes. Summary: All pIOLs available in the United States provide high-quality visual correction of moderate to high myopia and/or myopia with astigmatism. Proper follow-up for ECL and cataract formation is warranted.